0206 Rest-Activity Rhythms are Associated with Sleep Characteristics and Cognitive Functions in People with Heart Failure Over 6 Months. (25th May 2022) - Jeon, Sangchoon; Conley, Samantha; O'Connell, Meghan; Yang, Raymond; Redeker, Nancy
Abstract: Introduction: People with Heart failure (HF) often suffer from sleep deprivation and poor cognitive function. The purpose of this study was to examine the extent to which repeatedly measured rest-activity rhythms (RARs) measured with wrist actigraphy predict sleep characteristics and cognitive function in people with HF. Methods: We measured insomnia severity (ISI), sleep quality (Pittsburgh sleep quality index: PSQI), sleepiness (Epworth sleepiness scale: ESS), psychomotor vigilance (Psychomotor vigilance test: PVT), and quality of life (Euroqol 5D) among people with HF patients who participated in a randomized controlled trial of cognitive behavioral therapy for insomnia vs. HF self-management education at baseline, 3-, and 6-months post-intervention. We performed cosinor analysis with 24-hour rest-activity counts obtained with 7 days of wrist actigraphy at each time point and calculated the circadian quotient, which represents the strength of RARs. We used the Generalized Linear Mixed Model with random intercepts to examine the association between the circadian quotient, sleep characteristics, cognitive function, and quality of life after adjusting for time-group interactions over 6 months. Statistical significance for standardized coefficients was accepted at 5% type I error. Results: The analysis included 162 participants with HF and insomnia (Insomnia severity index >7) who completed actigraph monitoring for at least 7 days at baseline There was no significant change in the mean circadian quotient (Mean=0.78, SD=0.16) over 6 months. After adjusting for significant intervention effects, a greater circadian quotient was statistically associated with lower insomnia severity (-0.11±0.05), sleepiness (-0.12±0.05), sleep quality (-0.15±0.05), longer sleep duration (0.33±0.04) and better sleep efficiency (0.13±0.05). The circadian quotient was positively associated with cognitive function measured by fewer PVT lapses (-0.11±0.05) and quality of life (0.12±0.05). Conclusion: In addition to the significant intervention effects for insomnia, HF patients may benefited from strengthening RAR to improve sleep characteristics, cognitive function, and quality of life. Further research to assess the contributions of RAR in people who received the intervention for insomnia and the HF self-education separately is recommended. Support (If Any): R01NR016191 and P20NR014126